2013
DOI: 10.1186/1745-6215-14-293
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain and perioperative outcomes after laparoscopic radical hysterectomy and abdominal radical hysterectomy in patients with early cervical cancer: a randomised controlled trial

Abstract: BackgroundNon-randomised studies have suggested that the postoperative complications of (Campos LS, Limberger LF, Stein AT, Kalil AN) laparoscopic radical hysterectomy are similar to those in abdominal radical hysterectomy. However, no study evaluating postoperative pain comparing both techniques has been published thus far. Our objective was to compare pain intensity and other perioperative outcomes between laparoscopic radical hysterectomy (LRH) and abdominal radical hysterectomy (ARH) in early cervical canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…Twenty-two studies including 2922 cases (1230 LRH cases and 1692 ARH cases) met the inclusion criteria. Twenty-one publications were full-text articles, 15–36 and one publication was an abstract. 37 The references listed for these studies and review articles were also examined, but no further studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two studies including 2922 cases (1230 LRH cases and 1692 ARH cases) met the inclusion criteria. Twenty-one publications were full-text articles, 15–36 and one publication was an abstract. 37 The references listed for these studies and review articles were also examined, but no further studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of included studies, which included 1 small RCT 15 (Level of Evidence 2b), 15 retrospective studies, 16–29 , 37 and 6 prospective studies 30–33 , 35 , 36 comparing a contemporary series of patients (Level of Evidence 3b). Five studies examined cases with Stage IB1 or below disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared laparoscopic surgery for treatment of gynecologic diseases with abdominal or vaginal procedures, and their results support our findings. [27][28][29] The differences in the pain scores may have been due to two main reasons. First, laparoscopic surgery involves electrosurgical instruments for coagulation and dissection, whereas abdominal procedures involve clamps, scissors, and tying knots.…”
Section: Discussionmentioning
confidence: 99%
“…High quality evidence for the comparison of open versus the laparoscopic route of radical hysterectomy is lacking [3]. The only reported randomised controlled trial (RCT) included 30 women and revealed superior early postoperative pain outcomes in the laparoscopic arm at the expense of higher major complication rate [4]. An adequately powered RCT would require a sample size up to 1400 patients to detect differences in the safety outcomes between the two techniques [5].…”
Section: Introductionmentioning
confidence: 99%